EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE LEARNING DENGAN MENGGUNAKAN MEDIA KOKAMICABI TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK KELAS IV SEKOLAH DASAR NEGERI 02 BALEWANGI TAHUN PELAJARAN 2018/2019 - Lisna Sari; Risma Nuriyanti (Institut Pendidikan Indonesia Garut, 2020)
This research done for to find out the effectiveness of cooperative learning helps the media kokamicabi in speaking skills. The purpose of this study was to find the effectiviness of cooperative learning helps media kokamicabi in improving speaking skills. The research method used in this study is the experimental method. Research done, that is (1) cooperative learning model helps the media kokamicabi is effective in improving speaking skills with average pretest 54,4 while the average posttest is 74,4 higher than average ptetest (2)there is a difference in speaking skills by using cooperative learning model helps the media kokamicabi with conventional models. The results of the independent sampels t-test on the posstest value indicate the value of sig. (2-tiled) of 0.00 (p<0.05). The conclusion of this study is the cooperative learning model helps the media kokamicabi can improve speaking skills.